Karmaphala dan Cinta Kasih Dalam Satua Dadong Jepun - Mandra, I Wayan (Jayapangus Press, 2023)
Satua Bali is a literary work originating from local Balinese life. Satua-Satua Bali basically consists of two things, having its own aesthetic value and having human spiritual value, or basic truths that apply to everyone. Therefore, apart from being a medium for entertainment, Bali also has moral values ​​contained in it. This research aims to analyze religious moral teachings, especially karmaphala and the teachings of love in Satua Dadong, Japan. This research uses a qualitative type of research using a descriptive analysis approach. The results of this research show that in Satua Dadong Jepun there is a karmaphala teaching, where someone who always does good will be accepted. In Satua, one part of karmaphala is reflected, namely prarabda karmaphala. The teaching of love in Satua Dadong Jepun is that humans should always be compassionate towards each other, whatever the circumstances, as social creatures humans should always share love without discriminating between statuses because this will be able to create inner peace. In Satua, the Tri Hita Karana teachings and part of the Catur Paramitha teachings, namely Karuna, are also reflected.